Role of Antioxidants in Cooled Liquid Storage of Mammal Spermatozoa - Miguel A. Silvestre; Jesús L. Yániz; Fernando J. Peña; Pilar Santolaria; María Castelló-Ruiz (MDPI AG, 2021)
Cooled preservation of semen is usually associated with artificial insemination and genetic improvement programs in livestock species. Several studies have reported an increase in reactive oxidative species and a decrease in antioxidant substances and sperm quality parameters during long-term semen storage at refrigerated temperatures. The supplementation of antioxidants in extenders before refrigeration could reduce this detrimental effect. Various antioxidants have been tested, both enzymatic, such as superoxide dismutase and catalase, and non-enzymatic, such as reduced glutathione, vitamins E and C and melatonin. However, the problem of oxidative stress in semen storage has not been fully resolved. The effects of antioxidants for semen-cooled storage have not been reviewed in depth. Therefore, the objective of the present study was to review the efficiency of the supplementation of antioxidants in the extender during cooled storage of semen in livestock species.